An Effective Supervision Model of a Standard Clause for Consumer Protection in the Business Transactions - M. Syamsudin; M. Bekti Hendrie Anto; M. Nur Laili Dwi Kurniyanto; Intan Puspitasari (Hasanuddin Law Review, 2017)
This research aims to form an effective supervision model of a standard clause to protect consumer’s rights and interests. This study answers the questions the effectiveness of a standard clause supervision carried out by Otoritas Jasa Keuangan [Financial Services Authority (OJK)] and Badan Penyelesaian Sengketa Konsumen [Consumer Dispute Settlement Agency (BPSK)]; effective supervision model of a standard clause which can protect the rights and interest of the consumer. The object of this study are OJK and BPSK as a supervision of a standard clause. The result of this research shows that the supervision of standard clause done by those institutions has not been effective yet, this caused by several factors to wit the weakness of implementing regulation in terms of supervision, unclear supervision mechanism, the weakness of socialization related to the rules of standard clause towards business actors, and other weakness and obstacles faced by both institutions. The effective supervision model of standard clause is being formed that based on five points, namely: (1) the needs of institution/agency reformation who authorize to do supervision of standard clause; (2) the needs to determine the scope of duty and authority of standard clause supervision institution; (3) the needs of determination of material range about standard clause subjected to supervision which comprises: the content, the form, the position and the expression; (4) the needs of precise mechanism of standard clause supervision conducted by supervision institution; (5) the needs of following up the supervision results, especially to the business actors who break the standard clause rules.